Cloud-Native Telecom in Education: Bridging Digital Divides with VoIP - Munnaluru, Pardhiva Janardhana Krishna (International Journal of Computing and Engineering, 2025)
The digital divide in education persists as a critical global challenge, particularly affecting remote and underserved communities with limited connectivity infrastructure. Cloud-Native Telecom for Education Framework (CNTEF) offers a transformative solution by leveraging containerized network functions to deliver affordable, scalable Voice over IP services optimized for educational environments. This framework implements lightweight telecommunications components through Kubernetes orchestration, enabling deployment across diverse educational contexts from rural schools to universities. CNTEF supports essential educational applications, including remote lecture delivery, virtual tutoring, and collaborative learning environments, while addressing critical privacy, security, and equity considerations. By optimizing voice communication for limited-bandwidth environments and providing flexible deployment models, CNTEF creates accessible telecommunications infrastructure that bridges digital divides and expands educational opportunities. Implementation strategies emphasize integration with existing educational ecosystems, contextually-appropriate deployment approaches, and comprehensive policy frameworks that ensure responsible governance while maximizing educational impact.